The human genome and sport, including epigenetics and athleticogenomics: A brief look at a rapidly changing field - Sharp, N. C. C. (Journal of Sports Sciences, 2008)
Since Hugh Montgomery discovered the first of what are now nearly 200 "fitness genes", together with rapid advances in human gene therapy, there is now a real prospect of the use of genes, genetic elements, and/or cells that have the capacity to enhance athletic performance (to paraphrase the World Anti-Doping Agency's definition of gene doping). This overview covers the main areas of interface between genetics and sport, attempts to provide a context against which gene doping may be viewed, and suggests a futuristic legitimate use of genomic (and possibly epigenetic) information in sport.